2006
DOI: 10.1057/palgrave.jit.2000078
|View full text |Cite
|
Sign up to set email alerts
|

An Agent–Based Model of the Impact of Computer–Mediated Communication on Organizational Culture and Performance: An example of the Application of Complex Systems Analysis Tools to the Study of CIS

Abstract: Organizations that make use of computer information systems (CIS) are prototypical complex adaptive systems (CAS). This paper shows how an approach from Complexity Science, exploratory agent-based modeling (ABM), can be used to study the impact of two different modes of use of computer-mediated communication (CMC) on organizational culture (OC) and performance. The ABM includes stylized representations of (a) agents communicating with other agents to complete tasks; (b) an OC consisting of the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
0
14
0
2
Order By: Relevance
“…Since generally ABMs' outputs are nondeterministic time series [1] ). These expressions involve that the fitness function of the GA must calculate the expected value of the difference in mean and standard deviation between points of the time series generated by the ABM and the corresponding ones of the real system.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…Since generally ABMs' outputs are nondeterministic time series [1] ). These expressions involve that the fitness function of the GA must calculate the expected value of the difference in mean and standard deviation between points of the time series generated by the ABM and the corresponding ones of the real system.…”
Section: State Of the Artmentioning
confidence: 99%
“…Agent-Based Models (ABMs) (among other tools) are particularly well-suited to studying Complex Adaptive Systems (CAS) [1], cf. [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of recent empirical papers pertaining to the various applications of agent-based simulations such as knowledge exchange (Wang et al 2009), social activity generation and scheduling (Ronald et al 2012), computermediated communication (Canessa and Riolo 2006), innovation diffusion within market networks (Bohlmann et al 2010), and innovation networks (Ahrweiler et al 2011). Table 13.1 provides examples of these research studies.…”
Section: Background Literaturementioning
confidence: 99%
“…The ability of senior leadership to understand the potential cultural challenges is key in mitigating cultural resistance. Canessa and Riolo (2006) studied how different implementations of computer-mediated communication would strengthen or dilute organizational culture, leading to differences in communication effectiveness. In their study, IT was shown to be able to have a direct impact on the resilience of culture over time.…”
Section: Embeddednessmentioning
confidence: 99%